The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cmdc.202200385
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine‐Modified Ketoconazole Derivatives Show Increased Activity against Fungal and Trypanosomatid Pathogens

Abstract: Ketoconazole (KTZ) is an imidazole drug applied topically to treat numerous skin infections. However, as a systemic antifungal, KTZ′ efficacy and safety no longer justify its use as a first‐line treatment. Azole conjugates often display higher solubility and better antifungal activities than their parent azoles. Accordingly, we aimed at developing suitable linkers for clickable azole conjugation with a second antifungal molecule, and targeted drug delivery towards improving antifungal activity. For its low pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Their activity is partly attributed to inhibition of CYP51 (sterol 14αdemethylase) activity, which is because the azole part responsible for enzyme binding is not modified. 17 A similar effect is also attributed to quinolidine-2,4-thiazolidinone derivatives (Figure 2c), for which the molecular docking study suggested their affinity for 14α-demethylase. 18 Meanwhile, studies on the effect of chemical modification on the antifungal activity of indole-triazole conjugates (Figure 2d) showed that structures containing a phenyl substituent (R1) achieved MIC values analogous to those of fluconazole (MIC 250 μg/mL) against C. albicans.…”
Section: Modifications Of the Most Commonly Usedmentioning
confidence: 55%
See 3 more Smart Citations
“…Their activity is partly attributed to inhibition of CYP51 (sterol 14αdemethylase) activity, which is because the azole part responsible for enzyme binding is not modified. 17 A similar effect is also attributed to quinolidine-2,4-thiazolidinone derivatives (Figure 2c), for which the molecular docking study suggested their affinity for 14α-demethylase. 18 Meanwhile, studies on the effect of chemical modification on the antifungal activity of indole-triazole conjugates (Figure 2d) showed that structures containing a phenyl substituent (R1) achieved MIC values analogous to those of fluconazole (MIC 250 μg/mL) against C. albicans.…”
Section: Modifications Of the Most Commonly Usedmentioning
confidence: 55%
“…Thus, antifungal activity is accompanied by mitochondrial dysfunction and elevated levels of reactive oxygen species . The piperazine ring has also been used to modify the structure of ketoconazole (KTZ) . Of the 16 compounds, four (Figure b) showed antifungal activity equal to or superior to that of the parent compound (KTZ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of choice for the diseases is based on the use of antifungal drugs such as voriconazole, itraconazole, posaconazole, ketoconazole, thiabendazole and more recently, isavuconazole. As a matter of fact, in the literature, it is often confused as a genus/species studied in studies with ketoconazole, other antifungals or plant secondary metabolites [2,4,5,8].…”
Section: Introductionmentioning
confidence: 99%